Editorial: Navigating Transformation: Policy Shifts, Student Support, and the Future of Higher Education in Australia and New Zealand - Caroline Rueckert (JANZSSA)
JANZSSA Editor-in-Chief situates the papers in the latest issue within a transformitive year for higher education policy in Australia and New Zealand.